Prebiotic Intervention in Chemotherapy Induced Adverse Effects A Systematic Review- Muscle Wasting and Gut Health as Major Thrust - Rashmi C. Yadav; Santosh S. Bhujbal; Jayashree Mahore; Aarati Supekar (Journal of Coastal Life Medicine, 2023)
Background: Cancer is the world's leading cause of death and considered as life threatening disease. Its treatment usually includes chemotherapy, radiotherapy, surgery, or combination of the therapies. However, most preferred is chemotherapy which can be applied at the early stage as well as late stages of the disease. The development of adverse effects from chemotherapy impedes therapeutic utilization and significantly impacts cancer patients' quality of life. Muscle wasting, gastro intestinal inflammation, cardiotoxicity neurotoxicity and nephrotoxicity to name a few. Objective: To lessen the discomfort brought on by chemotherapy, traditional medications including antiemetic, multivitamins, diuretics, and antidiarrheal are recommended. However, these are known for secondary adverse effects as insomnia, hallucinations, intestinal cramping, etc. Natural drugs complementary and alternative therapies are employed to counteract these; however they lack scientific support and vary depending on the patient's personality. Certain contemporary approaches, such the use of probiotics and prebiotics, have been demonstrated to be effective in overcoming these disorders. Evidently, skeletal muscular atrophy and weakness are the tell-tale signs of cachexia brought on by chemotherapy, which reduces treatment tolerance, impairs daily functioning, and worsens survival in cancer patients. These conditions are referred to as sarcopenia and cancer cachexia. These therapies can also cause mucositis, a disorder marked by gastro-intestinal inflammation and disruption of the gut flora. Methods: Findings of different researcher in this thrust are analyzed and outcomes are summarized. This review focuses to examine the known mechanisms of prebiotic action and explores their potential to reduce the severity of chemotherapy-induced with primary focus on muscle wasting and gastro intestinal inflammation. Result and conclusion: The prebiotics are found to be effective in combating this chemotherapy induced adverse effects evidently focusing on the muscle wasting and GI inflammation. With a detailed literature survey, we conclude that this review will surely provide firm and better insights to the researchers to develop relevant option of prebiotics and establishing the possible mode of action.